Time Course of Muscle Damage and Inflammatory Responses to Resistance Training with Eccentric Overload in Trained Individuals - Bernardo Neme Ide; Lázaro Alessandro Soares Nunes; René Brenzikofer; Denise Vaz Macedo (Mediators of Inflammation)
The purpose of this study was to observe the time course of muscle damage and inflammatory responses following an eccentric overload resistance-training (EO) program. 3 females (23.8 ± 2.6 years; 70.9 ± 12.7 kg; 1.6 ± 0.08 m) and 5 males (23.8 ± 2.6 years; 75.1 ± 11.2 kg; 1.8 ± 0.1 m) underwent thirteen training sessions (4 × 8–10 eccentric-only repetitions—80% of eccentric 1RM, one-minute rest, 2x week−1, during 7 weeks, for three exercises). Blood samples were collected prior to (Pre) and after two (P2), seven (P7), nine (P9), eleven (P11), and thirteen (P13) sessions, always 96 hours after last session. The reference change values (RCV) analysis was employed for comparing the responses, and the percentual differences between the serial results were calculated for each subject and compared with RCV95%. Four subjects presented significant changes for creatine kinase at P2, and another two at P13; six for C-reactive protein at P2, and three at P11; two for neutrophils at P2, P4, and P13, respectively; and only one for white blood cells at P2, P4, P7, and P9, for lymphocyte at P7, P9, and P13, and for platelet at P4. We conclude that EO induced high magnitude of muscle damage and inflammatory responses in the initial phase of the program with subsequent attenuation.